Endophytic bacteria improve mesorhizobial nodulation, plant growth and yield in chickpea (Cicer arietinum) - SWARNALAKSHMI, KARIVARADHARAJAN; RAJKHOWA, SUSHMITA; POONIYA, VIJAY; ANNAPURNA, KANNEPALLI (The Indian Journal of Agricultural Sciences, 2021)
The aim of our study was to determine the symbiotic effectiveness of Mesorhizobium ciceri and plant growth promotion of endophytic bacteria in field-grown chickpea during 2016-17 and 2017-18. Co-inoculation of M. ciceri along with various endophytes has significantly improved soil dehydrogenase activity in chickpea rhizosphere. The combined inoculation of M. ciceri with nodule endophytes, viz. Bacillus cereus (25.7-51.9%) and Bacillus aerophilus (18.6-27.8%) showed higher nodule weight than uninoculated control which is at par with inoculation of M. ciceri with root endophyte (Pseudomonas flourescens). Co-inoculation of M. ciceri + B. aerophilus increased chickpea growth (13.7-21.5%) at 50% flowering stage and grain yield (15.6-18.2%) at harvest stage which is at par with the treatment with P. flourescens (17.5-20.1%). A positive correlation was observed between nodule dry weight with growth and yield of chickpea in the second year. Co-inoculation of endophytic bacteria has improved the symbiotic efficiency, growth and productivity of chickpea through synergistic interaction with Mesorhizobium.